Study of Marine Ecotourism Potential in Balai Island Aceh Singkil Regency of Aceh Province - Mulyadi, Aras; Nasution, Syafruddin; ', Agusriadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Marine tourism is all activities undertaken to create a fun, challenges, new experiences, and health that can only be done in the territorial waters. The study was conducted in June - July 2013 on the Balai Island of Aceh Singkil Regency, the Province of Aceh. The aims of the study were to determine the marine ecotourism potential and to formulate a strategy development of Balai Island. The method used in this study is a survey method, with respondents comprising of local people, tourists, business tourism stakeholders and policymakers. There were seven station observeds interen of water brightness, temperature, salinity, acidity, (pH), and the flow velocity carried.The results showed that the object and the potential appeal of ecologically Balai Island is a white sand with clear waters and coral reefs have great beauty, as well as activities that can be done such as fishing, snorkeling and enjoy activities such as walking around the island. From the SWOT analysis, it can be recommended as many as ten nautical tourism development strategies in the island: 1) optimization (travel packages), 2) to increase the easy transportation to get to the island, 3) to create a collaboration with the universities in research and conservation, 4) to provide counseling role and function of the importance of protecting the environment, 5) to create a bulletin board in the form of banners, pamphlets and the like to the areas that you can reach and make the print media and social media for external promotion, 6) to improve the quality of human resources, especially skills needed for ecotourism activities, 7) to increase the assurance of safety for tourists such as installing Tsunami alarms, 8) to intensity monitoring and enforcement of regulations in protecting the environment, 9) to empower the local communities in tourism promotion and marketing at the same time travel, and 10) to recom a zonation of activities of tourism.Keywords: Potential, Marine Ecotourism, Balai Island, Aceh Singkil